The US government’s use of soft power to combat terrorism: A strategy of political communication in Iraq - SAUD ALWAJAAN AL-SHAMMARI (Journal of Advanced Research in Social Sciences and Humanities, 2021)
Aim: This research paper aims to evaluate the effectiveness of American political communications abroad in the fight against terrorism through the lens of soft power. Furthermore, this article explores the government’s potential media use on the front lines of the anti-terrorist struggle. It also discusses the various definitions of soft power and offers advice to any leader concerned about the potential damage to their country’s international standing due to a failure to employ such strategies. Methodology: A case study methodology was used for the data collection and analysis in this study, indicating that it is a qualitative investigation. This paper thoroughly examines the case study of the Iraq invasion. The study focused on the two most widely read US news outlets. Because of their prominence in reflecting the views of the two largest political parties in the United States, the Democrats and the Republicans, CNN and Fox News are chosen. Findings: Research results reveal on how specific countries and media outlets use communication to advance soft power are also included. Implications/Novel Contribution: The research paper has successfully provided data on the adverse effects of using hard power, as seen in the fallout from the invasion of Iraq in the years 2001-2005. This was an act of vengeance for the attacks on September 11 that rocked the United States to its core. Discusses the effectiveness of employing soft power in combating terrorism.